2020
DOI: 10.1186/s12933-020-01014-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of twice-daily exenatide and insulin on carotid intima-media thickness in type 2 diabetes mellitus patients: a 52-week randomized, open-label, controlled trial

Abstract: Background: Exenatide, a glucagon like peptide 1 analog, has been suggested to reduce the cardiovascular disease risk factors, such as body weight, blood pressure and subclinical atherosclerosis in patients with type 2 diabetes mellitus (T2DM). This was the first randomized, open-label, controlled trial to compare the effects of exenatide versus insulin on subclinical atherosclerosis, as assessed by carotid-intima media thickness (CIMT), in patients with T2DM. Methods: A total of 66 patients with T2DM admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Exenatide was the first commercialized drug developed as the GLP-1 mimetics. Clinical evidence substantiating exenatide is an efficacious agent to treat T2DM with abnormal lipid metabolism ( 39 , 40 ). Gonza´lez-Ortiz et al.…”
Section: Discussionmentioning
confidence: 99%
“…Exenatide was the first commercialized drug developed as the GLP-1 mimetics. Clinical evidence substantiating exenatide is an efficacious agent to treat T2DM with abnormal lipid metabolism ( 39 , 40 ). Gonza´lez-Ortiz et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that exenatide once weekly improved CIMT, for the first time in the literature [14]. A more recently published study showed that exenatide treatment could prevent atherosclerosis progression in patients with T2DM compared to insulin therapy [31]. We showed that exenatide treatment for 6 months decreased CIMT significantly in obese patients with T2DM.…”
Section: Discussionmentioning
confidence: 60%
“…Patients. This was a retrospective cohort study using data from our randomized clinical trial that investigated the effects of exenatide, administered twice daily, combined with metformin when compared to insulin on carotid intimamedia thickness (cIMT) in patients with T2DM [23]. The original study was performed in accordance with the Declaration of Helsinki, and the study protocol was reviewed and approved by the Research Ethics Committee of Beijing Hospital (No.…”
Section: Methodsmentioning
confidence: 99%